Methods of valorization of natural resources. Part 1. Application in the nature protection - Matyjasiak, Piotr (Studia Ecologiae et Bioethicae, 2012)
The aim of this paper is to review the method of valorization of natural resources as applied in nature protection and spatial planning. Various valorization indices are discussed, including natural resources of special protection concern (species and natural habitat types of community interest, species legally protected in Poland, species, and ecosystems included in red lists, keystone species, flagship, and charismatic species), indicators of the conservation status of ecosystems and landscapes (indicator species and other indices of the degree of naturalness of ecosystems and landscapes), and components of ecological networks (ecological corridors and patches). Emphasis was placed on the need to include issues of ecological connectivity in the valorization of natural resources.